Experimental Analysis of an Instrumented Charpy Impact Using Statistical Study Based Data Analysis - Ali, Mohd Basri (Universiti Malaya, 2011)
The dynamic fracture initiation toughness and the characteristics are evaluated by using the instrumented charpy impact testing. The standard charpy impact machine is experimentally studied using the relevant data acquisition system in order to obtain the impact response. Strain gauges were connected to the data acquisition set and it was then attached to the charpy striker for the signal collection. Aluminium 6061 and low carbon steel 1050 were used in this testing. In this work, statistical based analysis has been performed using I-kaz method. In addition the power spectrum density (PSD) approach was then used for the energy based observation and a signal was converted from the time domain to the frequency domain using the fast Fourier transform (FFT) method. Comparison between experimental findings with related parameters such as of different materials, strain signals pattern, PSD and I-kaz, were finally correlated and discussed. It was found that the modulus of elasticity was related to the energy absorbed, strain signals amplitude, I-kaz coefficients and PSD. Finally, it is suggested that the properties of materials and the impact signals pattern is suitable to be analysed using the signal processing approach.